2019
DOI: 10.1016/j.nicl.2019.101705
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure correlates of general and specific second-order factors of psychopathology

Abstract: Increasing data indicate that prevalent forms of psychopathology can be organized into second-order dimensions based on their correlations, including a general factor of psychopathology that explains the common variance among all disorders and specific second-order externalizing and internalizing factors. Nevertheless, most existing studies on the neural correlates of psychopathology employ case-control designs that treat diagnoses as independent categories, ignoring the highly correlated nature of psychopatho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 65 publications
1
5
1
Order By: Relevance
“…Our findings partly contrast prior literature 3,16 . We propose several explanations for our results.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Our findings partly contrast prior literature 3,16 . We propose several explanations for our results.…”
Section: Discussioncontrasting
confidence: 93%
“…have not yet occurred or are less prominent in children at a given age. Cross-sectional studies have generally shown that higher psychiatric symptoms are associated with lower FA and higher MD [15][16][17] . However, our understanding of the longitudinal relation between neuro-and behavioral development is limited by a dearth of well-powered longitudinal studies with repeated measurements 18 and by the overlooking of how brain and behavior relate to each other over time.…”
Section: Text Introductionmentioning
confidence: 99%
“…This may be an early marker of transdiagnostic relevance, as suggested by a review indicating that WM pathology, especially that affecting the corpus callosum, is shared across several neuropsychiatric disorders ( Sagarwala and Nasrallah, 2020 ); this conclusion was also supported by a recent mega-analysis ( Koshiyama et al, 2020 ), making the corpus callosum a promising structural candidate underlying a high-order psychopathology “ p ” factor ( Caspi and Moffitt, 2018 ). Another study using a latent factor approach further demonstrated that the properties of the corpus callosum are related to general psychopathology, while second-order factors are reflected in abnormalities of more specific WM tracts ( Hinton et al, 2019 ). Compromised WM integrity in the splenium may represent not only a biomarker, but also a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…We observed differences in FA, MD and RD in PDE compared to controls in this region, a difference in RD suggesting altered myelination. Given the importance of the sagittal stratum in terms of connections, alteration of white matter integrity in this tract bundle may have widespread implications for effective integration of numerous functions including emotional processing, regulation of mental distress, sensory and motor function (Hinton et al 2019;Juttukonda et al 2019;Patel et al 2018;Poletti et al 2020). One prior study in neonates found sex-by-symptom interaction effects for FA in the sagittal stratum for a composite of prenatal depression and anxiety (Dean et al 2018).…”
Section: Discussionmentioning
confidence: 99%